Future-Labs in the Classroom: The Experience of -skopìa. (December 2018) - Emanuelli, Chiara; Scolozzi, Rocco; Brunori, Francesco; Poli, Roberto
During the past three years, -skopìa[EDUCATION], the educational branch of the recently established start-up of the University of Trento, -skopìa, has conducted an extensive series of future laboratories in the classroom, working in particular with students aged twelve years old (second year of "medie inferiori") and fifteen years old (second year of "medie superiori"). Future labs follow an explicit protocol (initial and final tests, three major steps, respectively, focused on the past, the future and the present). Teachers wanting to conduct a lab in their classroom must attend a preliminary training course. Furthermore, all the labs are monitored by -skopìa.